Nonfragile State Estimator Design for Memristor-Based Fractional-Order Neural Networks with Randomly Occurring Hybrid Time Delays and Stochastic Cyber-Attacks - Qifeng Niu; Xiaoguang Shao; Yanjuan Lu; Yibo Zhao; Jie Zhang (Fractal and Fractional, 2025)
This paper addresses the design of nonfragile state estimators for memristor-based fractional-order neural networks that are subject to stochastic cyber-attacks and hybrid time delays. To mitigate the issue of limited bandwidth during signal transmission, quantitative processing is introduced to reduce network burden and prevent signal blocking. In real network environments, the outputs may be compromised by cyber-attacks, which can disrupt data transmission systems. To better reflect the actual conditions of fractional-order neural networks, a Bernoulli variable is utilized to describe the statistical properties. Additionally, novel conditions are presented to ensure the stochastic asymptotic stability of the augmented error system through a new fractional-order free-matrix-based integral inequality. Finally, the effectiveness of the proposed estimation methods is demonstrated through two numerical simulations.